External compression headache during Covid-19 pandemic: a neglected entity - Santos, Erlene Roberta Ribeiro dos; Lal, Amos; Tardieux, Felipe Maia; Ribeiro, Elayne Cristina de Oliveira; Fortes, Henry Martins Soares; Valença , Marcelo Moraes (Headache Medicine, 2023)
Introduction Personal Protective Equipment (PPE) is part of the work routine of health professionals, especially during pandemics. During the Covid-19 pandemic, the use of PPE became constant for long working hours, resulting in adverse effects on the health of professionals, especially headache. Objective In this review, we explore the scientific literature on headache associated with prolonged use of PPE during the coronavirus pandemic. Method This is a narrative literature review conducted through the PubMed and Web of Science databases according to the following MeSH descriptors: “Face shield”, “Headache” and “Covid-19”. Articles that analyzed the presence of headache and other adverse events in health professionals in prolonged use of PPE were included. Results The included studies point to headache as the most prevalent adverse event, which may be a new headache or the worsening of a previous headache. Other effects were also found, such as pressure marks on the skin, hyperemia in contact areas; suffocation; reduced concentration and excessive sweating. Conclusion The use of PPE for long periods can cause headaches due to external pressure, in addition to other unwanted events.These effects reveal the importance of studies to make PPE more efficient, ensuring protection for the individual without causing discomfort.